Estabelecimento do ácaro-vermelho-das-palmeiras, Raoiella indica Hirst, sugere mudanças na ácarofauna dos folíolos de coqueiro. - Barros, Maria Edvânia Neves (2017)
The introduction and establishment of an invasive species in a new habitat represents one of the main threat to biodiversity and struture of ecosystem. A reecent exemple of a mite that became an invasive species is the red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae). After its introduction in the America, that species has considerably expanded the number of hosts, currently are listed more than 90 botanic species, being related as key pest of some these. Since its detection in the America, the focus of studies on this continent has been finding control measures for this species. The present study aimed to investigate the possibility of alteration in the acarine fauna of coconut leaflets (abundance and diversity) mediated by the introduction and establishment of R. indica. For this purpose a survey was carried over a period of one year in two areas of coconut cultivation, an area infested and another free of R. indica. The results of present study suggest that the introduction of the R. indica promote changes in the acarine fauna present in coconut leaflets. Diferences were detected in the abundance and biodiversity of mites at the level of taxonomic categories (family and species) and at the level of trophic groups (predators, herbivores and mites with undefined feeding mode). Additionaly, in plants infested by plants by invasive species was observed a similar standard of fluctuation of phytoseid mites and tenuipalpid mites (family to which the invasive species belongs). In that plants, the density of tenuipalpid mites was also the variable that most contribuided to explain the fluctuation of phytoseiid mites. Such evidences suggest that the invasive species, R. indica, acts as a keystone species structuring the acarine fauna in coconut plants.